Literacy, learning and ICT : - Cassidy, Bernadette (VDM Verlag Dr. Muller, 2009)
This book studies on the literacy and ICT relationship within mainstream schools; but little research on the same topic in special schools with children and young people with learning difficulties. Theories of learning suggest all students need a range of learning resources including ICT. The question is whether ICT has particular relevance for those with learning difficulties. The findings suggest a disparity between having an ICT policy and the practice of ICT. ICT was being taught rather than utilised as a teaching tool, furthermore, ICT did not appear to raise literacy levels, and in the absence of a comprehensive and holistic framework, ICT may lead to the erosion of some skills in other aspects of literacy. The author concludes with the recommendation of an evidence-based model for learning resources and support provision which is student-centred and describes a working model in practice